Using art to teach reading comprehension strategies lesson plans for teachers - Klein, Jennifer 1959-; Stuart, Elizabeth 1976- (Rowan & Littlefield Publishers, 2013)
"Using art to teach reading comprehension strategies: lessons plan for teachers will provide both classroom and art teachers with an overview of six different reading strategies and integrated reading and art lessons that they can implement in their own classrooms and schools. Addressing specific National Visual Art Standards, Common Core Standards for Reading, and National Reading Standards, this book is designed so that classroom and art teachers can work either in collaboration with visual arts teachers or independently, if school staff does not include a visual arts instructor. This teacher-friendly, easy-to-use book offers background information on the strategies and lessons that allow teachers to copy student materials and begin implementing this approach in their classrooms right away." - Provided by publisher